2008
DOI: 10.1159/000156711
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Vestibular Schwannomas after Surgery

Abstract: The issue of recurrence of vestibular schwannomas is poorly studied by the surgical literature and is probably underestimated. Our own long-term retrospective analysis after translabyrinthine approach has indicated a 9.2% recurrence rate. This long-term event is mainly due to regrowth of microfragments that have been left in the operative field along the course of the facial nerve or at the surface of the pons. Management of recurrence depends on the tumor size and patient's condition. Our current policy is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 4 publications
1
15
0
1
Order By: Relevance
“…We found that the VS recurrence rate in a large sample of ANA respondents was 14.5% and years since treatment and resection amount were the two independent predictors of recurrence. Various studies have reported a recurrence rate of 5% to 45% associated with different treatment modalities . The observed recurrence rate in this study is within the wide range of reported rates in the literature, which is likely due to its comprehensive patient‐centered and survey‐based nature.…”
Section: Discussionsupporting
confidence: 68%
“…We found that the VS recurrence rate in a large sample of ANA respondents was 14.5% and years since treatment and resection amount were the two independent predictors of recurrence. Various studies have reported a recurrence rate of 5% to 45% associated with different treatment modalities . The observed recurrence rate in this study is within the wide range of reported rates in the literature, which is likely due to its comprehensive patient‐centered and survey‐based nature.…”
Section: Discussionsupporting
confidence: 68%
“…2,8,12,24,25 We note that during our 28-year experience of managing VSs with SRS, 18% of our patients previously underwent 1 or more microsurgical resections.…”
Section: Resultsmentioning
confidence: 91%
“…7,13,20,22 The recurrence rate of VS has been shown to be 2.6%-11.0% after gross-total resection, and 20%-50% of VS tumors progress after subtotal resection. 1,2,12,19,20,22,24,25,26,28 Since the development of the Gamma Knife (GK) technology, stereotactic radiosurgery (SRS) has become an increasingly used alternative or adjuvant VS management tool that eliminates many risks associated with resection.14,23 Initial SRS for VS has improved hearing retention rates in 60%-90% of patients and reduced facial neuropa-ABBREVIATIONS GK = Gamma Knife; G-R = Gardner-Robertson; HB = House-Brackmann; QOL = quality of life; SRS = stereotactic radiosurgery; VS = vestibular schwannoma. The Center for Image-Guided Neurosurgery and the Departments of 1 Neurological Surgery and 2 Radiation Oncology, University of Pittsburgh Medical Center, Pittsburgh, Pennsylvania OBJECTIVE The goal of this retrospective cohort study was to assess long-term outcomes in patients with vestibular schwannoma (VS) who underwent stereotactic radiosurgery (SRS) after initial microsurgical resection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After this timetumor recurrence was theoretically possible but extremely improbable.Like us, Carlson et al 10 also recommend a repeat imaging at 15 years for linear enhancement during follow-up. Barring Roche et al [12]who reported 9.2% recurrence rate after TLA for VSwith a followup ranging from 8 to 16 years there have been no reports of recurrences after 10 years of follow-up, nor have been authors advocating a follow-up for greater than 10 years. However, considering that the incidence of long-term recurrence (after 10 years) after GTR of VS is still very low (2/2553 cases; 0.08%) the cost-benefit ratio of following up all VS for five more years must also be considered.…”
Section: Discussionmentioning
confidence: 99%